ANALISIS KOMPETENSI GURU MATA PELAJARAN AKIDAH AKHLAK ERA REVOLUSI INDUSTRI 5.0 DI MTs NEGERI 1 LANGKAT - Salmini; Zaifatur Ridha; Khairuddin YM (Jurnal Iqtirahaat, 2024)
Teachers must continue to improve their abilities related to the digitalisation of education. The type of research is qualitative research, data collection methods by means of observation, interviews, and documentation. Data analysis techniques with inductive analysis to find research results. The results of the study are the pedagogical competence that has been shown by the moral aqidah teacher where he is able to manage learning well where the moral aqidah teacher has understood all students, is able to plan and implement learning well. Another moral aqidah teacher competence is personality competence which is shown by an attitude that provides an example, according to what is said or taught with what is done. Furthermore, the professional competence that exists in moral aqidah teachers is mastering the material well. Moral aqidah teachers at MTs Negeri I Langkat have shown other competencies, namely social competence. This is evidenced by the ability of the moral aqidah teacher to build communication with students, teachers and all school residents.